Motivating Students Intrinsically Through ESP and Integration of Academic and Professional Skills in EMI Context - Khan, Rana (Advances in Social Sciences Research Journal, 2023)
While much research has been done on improving motivational levels among students, educators still struggle everyday trying to motivate students. There’s little or negligible evidence of research pointing to the role of ESP and integrated academic and communicative skills in improving intrinsic motivational levels among students. This report discusses a case study in a higher educational institute, in Kuwait where the low motivational levels in students encouraged the foundation program unit to explore whether incorporating ESP and academic skills in the foundation program can motivate students intrinsically to learn the language and thus support them in acquiring content in their diploma programs. The foundation unit designed a new foundation course, ESF (English and Skills Foundation) program to deal with amotivation and motivate students intrinsically. The new program aimed at aligning future goals of students to their current language learning in order to motivate them intrinsically under the EMI context. The program introduced two new components ESAP (English for Specific and Academic Purposes), Business English and IDEAS (Integrated Directions for English and Academic Skills), a course aimed at improving academic, communicative and computer literacy skills in students to prepare them for the globalized environment and learning they need so much in their EMI context. Closed ended questionnaires and open-ended focus group interviews were administered to foundation program students, both before and after the implementation of the program, to investigate any improvement in their motivational levels. The findings indicate that program was taken positively by students and showed improved motivational levels amongst students. The research findings revealed a new dimension wherein students employed learner strategies and integrated regulation pointing to improved intrinsic motivational levels as a result of the new ESF program. The new ESF program sets an example as a pilot project for other major programs of study.